Focus on Health Literacy: Recommendations to Improve European Union Risk Management Plan Public Summaries. (May 2015) - Wolka, Anne; Simpson, Katherine; Lockwood, Karen; Neuhauser, Linda
Background: The complexity of drug risk information often exceeds patients' abilities to understand and effectively act on it. Methods: The authors evaluated a layperson-focused European Union Risk Management Plan Public Summary and revised it to improve its understandability and usability by applying health literacy principles. The Suitability Assessment of Materials was used to test the appropriateness of the document for readers with low-to-average literacy levels. Two rounds of usability tests were conducted with American adults who had low to average education levels to identify areas of confusion. Revisions were made within perceived regulatory constraints. Results: A number of health literacy principles can be applied to improve the understandability and usability of the document; however, the document contains many inherently complex concepts. Conclusions: The authors recommend that stakeholders reassess the intended use of the document by members of the public and rethink its scope and structure, with close involvement of patients and caregivers.